2015
DOI: 10.1128/aac.04576-14
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Extended-Spectrum-β-Lactamase- and AmpC-Producing Enterobacteriaceae in Household Dogs

Abstract: A longitudinal study was performed to (i) investigate the continuity of shedding of extended-spectrum-beta-lactamase (ESBL)-producing Enterobacteriaceae in dogs without clinical signs, (ii) identify dominant plasmid-mediated ESBL genes, and (iii) quantify ESBL-producing Enterobacteriaceae in feces. Fecal samples from 38 dogs were collected monthly for 6 months. Additional samples were collected from 7 included dogs on a weekly basis for 6 weeks. Numbers of CFU per gram of feces for nonwild-type Enterobacteriac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 26 publications
(29 reference statements)
9
52
0
Order By: Relevance
“…1 Historically, ESBL-EC and pAmpC-EC infections have been associated with healthcare settings, 2 but their acquisition in the community has been increasingly reported in several countries since 2000-10. 3 Although a high prevalence of ESBL-EC and pAmpC-EC has been reported in livestock (particularly poultry), 4 chicken meat, 2 and companion animals, 5 their role as sources of human infection with ESBL-EC and pAmpC-EC remains controversial. 2,6,7 Human exposure to ESBL-EC and pAmpC-EC might occur via animals, food, the environment, and human-to-human transmission; however, their relative contributions are yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…1 Historically, ESBL-EC and pAmpC-EC infections have been associated with healthcare settings, 2 but their acquisition in the community has been increasingly reported in several countries since 2000-10. 3 Although a high prevalence of ESBL-EC and pAmpC-EC has been reported in livestock (particularly poultry), 4 chicken meat, 2 and companion animals, 5 their role as sources of human infection with ESBL-EC and pAmpC-EC remains controversial. 2,6,7 Human exposure to ESBL-EC and pAmpC-EC might occur via animals, food, the environment, and human-to-human transmission; however, their relative contributions are yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…There was a strong association between raw feeding and the likelihood of faecal shedding of E. coli exhibiting AmpC‐type resistance among therapy dogs in Canada over the course of 18 months (Lefebvre et al ). Two Dutch longitudinal studies reported associations between raw feeding and faecal E. coli from dogs showing ESBL resistance (Baede et al ) or faecal Enterobacteriaceae from cats showing ESBL/AmpC resistance (Baede et al ). This last study also found that, where phenotypically resistant Enterobacteriaceae were isolated, the mean count (colony‐forming units per gram faeces) for such isolates among raw‐fed cats was over two orders of magnitude higher than among controls.…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
“…In a study from Pennsylvania, failure to detect beta-lactamase genes in 20 out of 60 beta-lactam resistant E. coli isolated from companion animals was reported (O'Keefe et al, 2010). Several explanations had been put forward by many workers for the possible expression of resistant phenotype in the absence of betalactamase genes (Drieux et al, 2008 andBaede et al, 2015).…”
Section: Results and Discussion Isolation And Detection Of Beta-lactamentioning
confidence: 99%
“…One explanation could be the contribution of other resistance mechanisms, such as enhanced expression of efflux pumps (Sun et al, 2010 andBaede et al, 2015).…”
Section: Results and Discussion Isolation And Detection Of Beta-lactamentioning
confidence: 99%